Integration of Islamic Education and Entrepreneurship to Develop the Muslim's Economy in East Java - Sitepu, Rismawati Br; Utami , Christina Whidya; Sembiring , Murpin Josua; Nainggolan, Romauli; Pranoto, Henry Susanto (JOM, 2025)
This study explores how integrating Islamic education with entrepreneurship can support the economic development of Muslims. Islamic education, which emphasizes values ​​such as honesty, social responsibility, and perseverance, is believed to have the potential to shape an ethical entrepreneurial mentality. However, the integration between Islamic education and entrepreneurship has not been fully realized in practice, mainly due to the lack of a specific curriculum and systematic support from various parties. With a qualitative approach, this study uses an in-depth interview method with informants with a background in Islamic education and entrepreneurship. Informants were selected through purposive sampling to obtain an in-depth perspective. The results of the study indicate that the development of an Islamic curriculum, practical and field training, and the formation of an entrepreneurial mentality have an important role in building the character of ethical entrepreneurs, where values ​​such as honesty, social responsibility, and perseverance are the foundation for the mindset of Muslim entrepreneurs. In addition, this integration can potentially strengthen the Muslim economy by creating entrepreneurs based on moral values.